Global Financial Development Report 2013 : Rethinking the Role of the State in Finance - World Bank (Washington, DC, 2012)
The goal of this inaugural global financial development report is to contribute to the evolving debate on the role of the state in the financial sector, highlighted from the perspective of development. The report is aimed at a broad range of stakeholders, including governments, international financial institutions, nongovernmental organizations, think tanks, academics, private sector participants, donors, and the wider development community. The report offers policy advice based on research and lessons from operational work. The report benchmarks financial institutions and markets around the world, recognizing the diversity of modern financial systems. In its analysis of the state's role in finance, the report seeks to avoid simplistic, ideological views, instead aiming to develop a more nuanced approach to financial sector policy based on a synthesis of new data, research, and operational experiences. The report emphasizes that the state has a crucial role in the financial sector-it needs to provide strong prudential supervision, ensure healthy competition, and enhance financial infrastructure. Because the financial system is dynamic and conditions are constantly changing, regular updates are essential. Hence, this report should be seen as part of an ongoing project aimed at supporting systematic evaluation, improving data, and fostering broader partnerships. Future reports might address financial inclusion, the development of local currency capital markets, the financial sector's role in long-term financing, and the state's role in financing health care and pensions.